Dental fluorosis, dental caries, and treatment needs in Al-Muthana'a governorate among 12 years old students - Hiba A AL-Shuker; Athraa M AL-Waheb (College of Dentistry/ University of Baghdad, 2015)
Background: A case-control study design revealeda relationship between the present of fluoride, and the reduction of dental caries and the increase prevalence and severity of dental fluorosis .The aim of this study was to assess the prevalence and severity of dental caries in relation to dental fluorosis among school children in Al-Muthana'a Governorate. Materials and methods: It was conducted among primary school students aged 12 years old, the age was taken according to the criteria of World Health Organization (1997) (1).The number of students was selected in each sector of control group according to number of schools in that sector .Sectors of control group which depend on water of river as source of drinking water. Case group which include AL-Salman sector that depend on underground water as source of drinking water includestudents in all area of Al- Salman sector in 4 schools Results: Results showed that the prevalence of dental fluorosis in case group, is (60.6%) and the mean of maximal fluorosis index (1.15 ±0.12) .In control group, the prevalence of dental fluorosis is (49.0%) and the mean of maximal fluorosis index (0.73±0.4) .The DMFS/DMFT values of dental caries for case sample (3.83± 0.44) (2.31± 0.22), while for control DMFS/DMFT is (5.95±0.26) (3.41±0.13) respectively with significantly difference. The prevalence of caries free in case sample is 23.6% while for control is 8.4% with significantly difference between case and control. Conclusions:A study revealed that a high prevalence of dental fluorosis, dental caries thus there is a need for preventive programs among those children.